GAMBARAN TUGAS PERKEMBANGAN MAHASISWA PSIKOLOGI UNIVERSITAS ESA UNGGUL - Safitri, Safitri (Jurnal Psikologi : Media Ilmiah Psikologi, 2018)
Initial guidance with established structured Advisors (PAs) is not easy to recognize the personal issues involved in the learning process. The PAs have not fully served the role of mentor who must be able to understand his psychosocial guidance. For that we need more specific data especially on the task of student development. The purpose of this study is to see how the picture and the different tasks of the development of psychology students from each generation. The research method is quantitative descriptive and inferential different test result of student development task. Responde is a student of regular psychology and parallel EU Unggul Unggul force of 2015-2017. Measuring tool uses Student Development Assignment (ITP-PT) from Universitas Pendidikan Indonesia. The result of the research shows that the highest average of development task is psychology student of parallel 2016 which is 5,74 and the lowest is 2016 regular psychology student that is 5,50. The lowest aspect of the majority is aspect 2 (the basis of ethical behavior), and the highest aspect 7 (self-acceptance and development). There are 3 aspects that have below average values for each force ie aspect 2 (ethical behavioral basis), 3 (emotional maturity) and 4 (intellectual maturity), which is an internal aspect of the student. And there are 2 aspects above average for each force that is aspect 6 (social role as man and woman), and 7 (self acceptance and development), which is external aspect. The test result is different between aspect of developmental task of student with force, difference of developmental task of psychology student of each generation with value of sig (p) 0,0Â Keywords: developmental tasks, students, academic advisors